Soluble fms‐like tyrosine kinase to placental growth factor ratio in different stages of early‐onset fetal growth restriction and small for gestational age. (14th September 2020) - Garcia‐Manau, Pablo; Mendoza, Manel; Bonacina, Erika; Garrido‐Gimenez, Carmen; Fernandez‐Oliva, Antoni; Zanini, Julia; Catalan, Marina; Tur, Helena; Serrano, Berta; Carreras, Elena
Abstract: Introduction: Increased soluble fms‐like tyrosine kinase to placental growth factor ratio (sFlt‐1/PlGF) has been demonstrated in early‐onset fetal growth restriction (FGR) and small for gestational age (SGA). sFlt‐1/PlGF cut‐offs have been described to assess preeclampsia severity; however, sFlt‐1/PlGF values present in early‐onset SGA and different FGR severity stages remain unknown. Hence, the objective of this study was to describe and compare the sFlt‐1/PlGF values and pregnancy outcomes among early‐onset SGA/FGR stages. Material and methods: This is a prospective case‐control study conducted at Vall d'Hebron University Hospital. Singleton pregnancies with estimated fetal weight <10th centile and a control group of uncomplicated pregnancies between 20 +0 and 31 +6  weeks of gestation were enrolled. Study women were classified at diagnosis into different stages, according to estimated fetal weight centile and Doppler ultrasound. sFlt‐1/PlGF serum concentrations were measured at diagnosis and, together with pregnancy outcomes, were compared among FGR severity stages, SGA, and controls. Finally, correlations between sFlt‐1/PlGF values and time to delivery, gestational age at delivery, days of neonatal admission, and birthweight z ‐scores were investigated. Results: Among the 207 women enrolled, 32 (15.4%) had uncomplicated pregnancies, 49 (23.7%) pregnancies showed SGA, and 126 (60.9%) involved FGR (92 being stage I, 17 stage II, and 17 stage III). SGA and controls had similar median sFlt‐1/PlGF values (25.7 vs 27.1, P  > .05) and pregnancy outcomes. However, all FGR stages had significantly poorer outcomes and greater sFlt‐1/PlGF values than those of SGA and controls. Furthermore, median values differed significantly among all FGR severity stages (9.76 for stage I; 284.3 for stage II, and 625.02 for stage III, P  < .05) increasing with FGR severity as well as the frequency of adverse pregnancy outcomes. Additionally, a significant correlation was found between greater sFlt‐1/PlGF ratio values and gestational age at delivery, time from diagnosis to delivery, birthweight z ‐scores, and time in neonatal intensive care unit ( r  = −.637, r  = −.576, r  = −.161, and r  = .311, respectively). Conclusions: Values of sFlt‐1/PlGF at diagnosis permit early‐onset FGR/SGA severity classification with good correlation with Doppler ultrasound findings and the occurrence of adverse outcomes. Thus, sFlt‐1/PlGF could aid in early‐onset FGR/SGA severity classification and clinical management when Doppler assessment is not feasible.